Service Quality and Customers’ Trust, Moderating Role of Personality Traits (Sains Humanika, 2016)
Customers’ trust is an inevitable asset for organizations. The long-term relationship of customer-organization depends upon the presence of customers’ trust on the organization. It’s a delicate sense of feeling derived from quality and commitment of the organizations to meet customers’ expectations. The significance of this phenomenon in services industry becomes even more critical where organizations have to know individual as well as contextual factors that influence on customers’ trust. This study tested the impact of different dimensions of perceived service quality on customers’ trust and how this perception varies depending upon the personality disposition in life insurance sector of Pakistan. Using cross sectional research design, the study taped customers’ responses regarding service quality, customers’ trust, and their personality disposition. The sample was obtained from insurance sector in different cities of Pakistan, where 242 customers were participated in the survey Explanatory factor analysis, single mean T-test, correlation and hierarchical multiple regression analyses were used to test proposed hypotheses. The results indicate   positive relationship between different dimensions of service quality and customers’ trust. The finding of moderation analysis shows that customer’s personality traits have varied effects on the relationships between dimensions of service quality and customers’ trust. Finally, based on quantitative findings, proposed framework was revised. This study recommends several implications for managers of services industry so that they should develop an effective service design to build long-term customers’ trust in accordance with different personality traits.
Keywords: Dimensions of service quality; customers' trust; personality traits; insurance sector of Pakistan